Determining the Research Needs of Social Insurer: Using Analytical Hierarchy ‎Process (AHP)‎ - Mohammad Karim Bahadori; Fardin Mehrabian (Journal of Holistic Nursing and Midwifery)
Introduction: Research conducted without any need assessment not only helps solve problems but ‎also increase the current problems and result in waste of limited resources.